PENGARUH KEPRIBADIAN WIRAUSAHA DAN PENGETAHUAN AKUNTANSI PADA PENGGUNAAN INFORMASI AKUNTANSI DALAM PEMBUATAN KEPUTUSAN INVESTASI - Ari Maya Sari, Ni Made; Dwirandra, A.A.N.B (E-Jurnal Akuntansi; Vol 11 No 1 (2015), 2015)
Personality or self-employment is not necessarily a linear effect on the use of accounting information in investment decision-making, but there are contingency factors that influence in it, one of which is a accounting knowledgefactor. The purpose of this study was to determine whether there is influence of entrepreneurial personality and accounting knowledge on the use of accounting information in making investment decisions. This study used a sample saturated with a sample of 41 respondents who were enrolled in an entrepreneurial Business Incubator University of Udayana. The analysis technique used is MRA (Moderated Regression Analysis). Based on the results of the analysis found that the entrepreneurial personality variables and variable accounting knowledge has a positive and significant effect on the use of accounting information in making investment decisions. Moderated Regression Analysis showed that the variable accounting knowledge is moderating variables that strengthen entrepreneurial personality influences on the use of accounting information in making investment decisions.
Keywords: businessman personality, accounting knowledge, accounting information, Investment